Crowdsourcing delivery for fresh agricultural products in China—exploring the factors influencing individual participation - Li, Yanan; Gong, Yifei; Shui, Wenbing (Frontiers in Sustainable Food Systems, 2025)
As a new delivery model in China, crowdsourcing delivery for fresh agricultural products presents a promising approach to reducing both costs and losses linked to last-mile delivery. To attract more individuals to participate in crowdsourced delivery, we developed a model to examine the effects of expected reward (ER), expected cost (EC), trust (TR), risk (RI), social influence (SI), travel characteristics (TC), promotion conditions (PCs), and constraints (COs) on individuals’ participation willingness (PW) in crowdsourced delivery of fresh agricultural products. Based on the questionnaire data from 332 potential participants in China, we used structural equation modeling (SEM) to explore the influence paths. As hypothesized, expected reward, trust, and social influence positively affect individuals’ PW in crowdsourcing delivery, while expected cost (EC) has a negative effect. Additionally, we found that social influence exerts a significant indirect effect on participation by mediating trust. Based on these findings, we propose several practical recommendations to enhance participation in crowdsourcing delivery of fresh agricultural products. These include increasing the variety of rewards, establishing an interactive community within the crowdsourcing delivery app, and establishing a trust mechanism.